Sports Hernia and Athletic Pubalgia : diagnosis and treatment - Brunt, L. Michael; Diduch, David R. (Springer US, 2014)
Sports hernias are an increasingly recognized problem in athletics, presenting a challenge for team physicians and other health care providers regarding their diagnosis and management. Confusion is magnified by the various treatment methods that exist, both surgical and non-surgical. Sports Hernia and Athletic Pubalgia is the first text devoted solely to the topic of sports hernia and will examine its etiology and diagnosis, as well as how to differentiate it from other problems involving the athlete's hip area and other injuries it often correlates and interacts with, such as femoroacetabular impingement. It covers all current approaches to treatment, from open approaches to minimally invasive approaches, and discusses rehabilitation and return to play. Comprised of contributions from an international array of expert clinicians and thought leaders, this is the immediate authoritative book on the subject of sports hernias.